Performance Improvement Of Food Cluster Small Medium Enterprises (SMEs) In Magelang City - Budi Rahardjo; Khairul Ikhwan; Shinta Ratnawati; Hendi Ari Wibowo (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
During the pandemic, the turnover of the food cluster UKM, which is the mainstay of the Magelang City economy, has decreased. This study aims to describe the problems and performance of SMEs and determine the model for improving the performance of SMEs. This study uses qualitative research using The House Model. The research sample consisted of 17 UKM owners and 53 UKM employees. This research was conducted in three stages. The first stage is to identify the main problems faced by food cluster SMEs by using the fishbone chart. The second stage is to analyze the Importance-Performance aspect. The third stage is to design a model for improving SME performance with The House Model. The results of the study show that the main problem for SMEs is the low performance of SMEs in the food cluster. This low performance comes from 14 aspects originating from machines, methods, people, environment, and materials. The roof of the Pilot House is the vision of SMEs to become SMEs that are sustainable and competitive at the national level in five years.